User Experience of Older Adults With an Age-Friendly Transportation Planning E-Tool: Scoping Review - Bahrampoor Givi, Sara; Gagnon-Roy, Mireille; Pigot, Hélène; Provencher, Véronique (JMIR human factors, 2025)
Aging is associated with various challenges, especially concerning mobility. Transportation planning e-tools are currently available to provide older adults with real-time travel information and help them choose trip options. However, many older adults find them challenging to use, as they are not tailored to their specific needs, such as lack of accessibility to the different means of transportation. It is necessary to identify knowledge gaps about design based on older adults' experience using transportation planning e-tools. This study aims to identify knowledge gaps regarding the user experience design and its evaluation for older adults using transportation planning e-tools. A scoping review of the scientific literature was conducted, based on Arksey and O'Malley's guidelines. The search covers sources published in English from January 2002 to October 2022 through 7 scientific databases, including MEDLINE, AgeLine, CINAHL, SCOPUS, ProQuest, IEEE Explore, and TRID (Transportation Research International Documentation), and was updated in October 2023. Data selection and extraction were performed by the first author and were co-validated by 2 co-authors. The identified sources were analyzed based on source characteristics (authors, year of publication, title of the article, source of article, country, and context of the studies), the purpose of the studies (objectives and study orientation), and the mapping of the methodology and evaluation of user experience (design approach, setting, type of data collection and analysis, type of usability evaluation, and sample size). Both descriptive-analytical methods and thematic analysis were used to analyze the categorized data. Overall, 1905 sources were identified through databases, and 40 sources were selected for full-text analysis. Data analysis revealed in recent years that there has been significant growth in e-tools designed for older adults, but only 2 studies were related to the field of transportation. In total, 12 studies aimed to evaluate user experience, and 22 studies focused on a user-centered design approach. Most of these studies (n=31) were carried out in a laboratory setting, using summative usability evaluation (user-based testing). The System Usability Scale (SUS) was the most prevalent tool (15 studies) to measure user efficiency and satisfaction. However, no studies have been found that specifically aim to improve the mobility experience of older adults using an age-friendly transportation planning e-tool in a real-life context. There is a lack of studies assessing older adults' experience when using transportation planning e-tools in real-life situations. To bridge this gap, a participatory approach is necessary to better consider the needs of older adults in a real-life context and create age-friendly design guidelines for the development of transportation planning e-tools. This will not only enhance their user experience in trip planning but also promote their social engagement by improving their mobility.